2011
DOI: 10.1002/bdrb.20316
|View full text |Cite
|
Sign up to set email alerts
|

Lack of teratological effects in rats exposed to 20 or 60 kHz magnetic fields

Abstract: BACKGROUND: A risk assessment of magnetic field (MF) exposure conducted by the World Health Organization indicated the need for biological studies on primary hazard identification and quantitative risk evaluation of intermediate frequency (300 Hz–100 kHz) MFs. Because induction heating cookers generate such MFs for cooking, reproductive and developmental effects are a concern due to the close proximity of the fields' source to a cook's abdomen. METHODS: Pregnant Crl:CD(SD) rats (25/group) were exposed to a 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
1
24
2
Order By: Relevance
“…Consistent with reports in the literature, the observed changes were sporadic and did not affect organogenesis in the offspring [17]- [22]. Table 2.…”
Section: Reproductive Performance and Haematological Profilesupporting
confidence: 90%
“…Consistent with reports in the literature, the observed changes were sporadic and did not affect organogenesis in the offspring [17]- [22]. Table 2.…”
Section: Reproductive Performance and Haematological Profilesupporting
confidence: 90%
“…The MF exposure facility was explicitly described in a previous paper that also included a photograph (Nishimura et al, 2011). A pair of exposure facilities, one for 20 kHz and another for 60 kHz, were built in an area where the background 50 Hz MF was extremely low at <0.02 lT(rms).…”
Section: Magnetic Field Exposure Facilitiesmentioning
confidence: 99%
“…In another previous study in rodents (Nishimura et al, 2011), we exposed pregnant rats to IF MFs at 20 kHz in 0.2 mT(rms) and at 60 kHz in 0.1 mT(rms) during organogenesis for teratological evaluation. The present study in rats was performed in conjunction with the rat teratology study to cover an exposure period from pre-mating to implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Nishimura et al [27] found that exposure to intermediate frequency (300 Hz-100 KHz) magnetic fields during embryogenesis showed no teratogenic effect under experimental conditions. Foci of ossification when starting configuration in the normal bone development, the chondrocytes become enlarged and their cytoplasm vacuolated.…”
Section: Discussionmentioning
confidence: 98%